Exploring teachers’ beliefs about learning principles - Meij, Erik; Smits, Anneke; Meeter, Martijn (Frontiers in Education, 2025)
Teachers hold conscious or subconscious beliefs about pedagogy, education and learning that are deeply ingrained and steer their daily pedagogical reasoning. Numerous studies have aimed to reveal these beliefs, but whether specifically principles of learning are part of teachers’ beliefs has not yet been addressed. This study investigated whether teachers’ explicit and implicit beliefs are consistent with scientific principles of learning. For that purpose, a multiple-component online test was constructed. In an implicit word association task, participants had to categorize words as being linked with learning or not, with the responses and their speed analyzed for what they might reveal about beliefs about learning. In an explicit classroom statement task, participants were presented with a statement about actions in the classroom that either were or were not in line with principles of learning and asked how firmly they believed it was true (or false) and on what basis. Finally, in an explicit principle endorsement task, participants were asked how convinced they were that 10 principles of learning taken from an American Psychological Association consensus list were correct. A total of 257 pre-service and in-service teachers, teacher educators and educational scientists completed the test. Results showed that on average, 80% of the teachers did believe that the 10 principles presented were correct, although not all were endorsed with a high degree of conviction. In the implicit word association task, response times for words associated with learning were generally shorter than for other types of school related words. One principle, that adaptation of existing concepts is a slow process, was an anomaly on both tasks. Correlations between the implicit and explicit results were low. In conclusion, implicit and explicit responses reflect teacher beliefs about learning that are generally consistent with scientific learning principles, although the backing for some principles is less strong than for others.